Screening of blood glucose level as a key element of the strategy of prevention and early detection of type 2 diabetes mellitus - Liashko , Daria; Domanskyi, Rostyslav; Yanitska , Lesya; Horkunenko , Oksana; Yezhel , Iryna (The Ukrainian Scientific Medical Youth Journal, 2025)
the regular screening of glucose level in blood is important for prevention, early detection and treatment of type 2 diabetes mellitus. Timely detection of hyperglycemia, as the main index of impaired glucose metabolism, is a key aspect in prevention of development of long-term diabetic complications, including cardiovascular diseases, peripheral neuropathy, diabetic nephropathy, etc. Awareness of the risks of development of diabetic complications promotes the higher public awareness of the importance of healthy nutrition, regular physical activity, and a healthy lifestyle. The aim of the study was to carry out a blood glucose screening of individuals aged 18-21 years to analyze the impact of the risk factors of type 2 diabetes mellitus on the blood glucose levels, as well as to increase the awareness among higher education students about the importance of regular blood glucose screening for prevention of diabetes and prediabetic states. The level of glucose in capillary blood was determined using a glucometer with individual test strips, the data concerning the risk factors for diabetes taken in the form of a voluntary anonymous survey. According to the level of blood glucose the questionnaire of participants of the study were divided into two groups: group A - normoglycemia (the average blood glucose level is 4.6±0.5 mmol/l), group B – the elevated blood glucose (6.3±0.5 mmol/l). A statistical analysis of the questionnaire results and a quantitative assessment of the impact of risk factors for type 2 diabetes mellitus on the level of glycemia were performed. The homogeneity of gender composition of the groups of individuals with normoglycemia and elevated blood glucose levels was established. It was shown that having breakfast a few hours before the study did not influence the blood glucose levels among the individuals with normoglycemia. It was not possible to assess the effect of having breakfast on the level of glycemia in the group with elevated blood glucose levels due to insufficient sample size. The influence of the risk factors, such as the presence of unhealthy habits (smoking, consumption of energy drinks), heredity (having relatives with diagnosed diabetes mellitus), tendency to consume sweets and lack of regular physical activity, on the blood glucose levels of people of this age category was analyzed. It was shown that for people aged 18-21 years, heredity and lack of regular physical activity can be important risk factors for development of hyperglycemia. Having relatives with diagnosed diabetes mellitus increased the risk of hyperglycemia among the participants by 1.85 times; regular physical activity reduced the risk of hyperglycemia among the participants by 4.5 times.